The Boon and Bane of Covert Advertising - Viorela Dan; Sara Mahlmeister (University of Zurich, IKMZ - Department of Communication and Media Research, 2023)
When pharmaceutical companies operate disease-awareness websites, they are required to give complete and accurate information to consumers, but at the same time, they are seeking to increase revenue. In most countries, direct-to-consumer advertising for prescription drugs (DTCA) is prohibited; thus, such websites are among the few means by which pharmaceutical companies can communicate directly with consumers. Yet, our understanding of consumers' perceptions of such websites remains limited, especially in contexts where DTCA is disallowed. This research attempted to elucidate this issue via a qualitative mixed methods study, including an intervention, tasks, think-alouds, and open questions with German consumers (N = 46). Our results indicated that consumers' evaluations of a stimulus website about premature ejaculation, which were largely positive at first, changed when people became aware that it was operated by a pharmaceutical company. While respondents were cognisant of most or all the treatment options for the medical condition that were presented on the website, they were most aware of the availability of a prescription drug. Most were able to find out the name of that drug, which was not mentioned on the website, within minutes. We concluded that this form of covert advertising is best characterised as a double-edged sword.